Los títeres y la expresión de emociones en niños de la Institución Educativa Inicial N°70 Saramiriza 2022 - Montalvan Diburga, Diana Elizabeth (2024)
The main objective of this research was to determine the relationship between the use of puppets and the expression of emotions in children of the Institution Educative Initial N°70 Saramiriza 2022. To achieve this, a quantitative relational approach and a non-experimental design were used. specifically correlational and transactional. The population of interest included all children, and a census sample was chosen, totaling 66 participants. An observation guide was used as a tool for data collection. Validation was carried out through the evaluation of experts in the field. The results obtained showed a Rho Spearman correlation value rs= 1.000 (bilateral significance) = 0.068. With this result, the null hypothesis is rejected and the alternative hypothesis is accepted, at a significance level of 5%. Therefore, it is concluded that there is a statistically significant relationship between the use of puppets and the expression of emotions in the children of the Initial Educational Institution N°70 Saramiriza 2022.